Determination of barriers on the technology adoption among contractors in Malaysia / Ahmad Amirul Haziq Nordin and Nur’Ain Ismail - Nordin, Ahmad Amirul Haziq; Ismail, Nur’Ain (2023)
The decision making process of technology adoption is critical if one attempts to improve the present situation. It is generally accepted that construction is a risk-averse industry when it comes to new methods. Therefore, the objective of this research to determine barriers on the technology adoption implementation among contractor. However, construction workers have the belief that those who do not perform activities directly on the job site do not grasp the nature of the profession. As a result, there is a pervasive aversion to change and technology in the workplace and the construction industry continues to be a barrier to technology adoption. The research employs a quantitative method involving the distribution of a questionnaire survey among selected contractor company at construction companies in Kinta, Perak, Malaysia. The response rate was 98% from the sample size of 107. The findings indicated that the most significant aspect for the contractor companies is allocating funds for employee training to effectively embrace the use of new technology. In conclusion, embracing technology in the construction industry can significantly facilitate construction work and ensure smoother project execution. Overcoming the aversion to change and fostering a culture of technological openness will pave the way for progress and innovation in the construction sector.